Penerapan Digital Marketing pada Era Digital melalui Media Sosial di UMKM Yuk Ngopi Coffee Kota Medan - Veri Sangap Tua Pasaribu; Rouli Elisabet Naibaho; Ega Grace Nichol Sitindaon; Lisa Dwi Cahaya Nayu; Fadli Agus Triansyah (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze the application of digital marketing through social media at Yuk Ngopi Coffee UMKM in Medan City in facing competition in the digital era. The research method uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results show that the use of digital platforms, particularly Instagram and TikTok, contributes significantly to increasing brand awareness, consumer engagement, and market expansion. Content strategies that emphasize visual aesthetics, interaction with consumers, and affordable prices are key factors in attracting customers. In addition, the integration of offline experiences in the form of a café atmosphere with online promotions has succeeded in strengthening the brand image. However, the study also found several challenges, including limited human resources, marketing budgets, and the rapidly changing dynamics of social media algorithms. Theoretically, these findings reinforce the relevance of the Integrated Marketing Communication (IMC) model, Customer Relationship Management (CRM), and the concept of Perceived Value in the context of UMKM. This research provides practical implications for businesses to optimize social media as a strategic marketing tool, while balancing digital innovation and real-world consumer experiences.